(untitled) (JOSAR (Journal of Students Academic Research), 2025)
This research and development study aims to create a valid bioplastic learning medium for marine invertebrates, tailored to students’ needs in identifying animals in animal taxonomy courses. Marine invertebrates, particularly those from the Gastropod class, were collected through exploratory research along the southern coast of Blitar, preserved in resin, and supplemented with morphological characteristics. The study follows the 4D development model (Define, Design, Develop, Disseminate) proposed by Thiagarajan (1974). In developing the product, the researchers conducted material validation, media validation, and practicality testing. Two lecturers carried out the validation process, and the data obtained was analyzed using quantitative descriptive methods. The validation results showed scores of 0.80 for material and 0.84 for media, both classified as high. Therefore, the bioplastic learning media for marine invertebrates can be utilized to assist students in identifying animals and achieving learning objectives. However, further testing is required to ensure its effectiveness in enhancing students’ skills.